The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/designs4010003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Tip Leakage Flows in a Roots Blower

Abstract: Computational fluid dynamics (CFD) can help in understanding the nature of leakage flow phenomena inside the rotary positive displacement machines (PDMs). However, due to the lack of experimental results, the analysis of leakage flows in rotary PDMs by CFD has not yet been fully validated. Particle image velocimetry (PIV) tests with a microscopic lens and phase-lock were conducted to obtain the velocity field around the tip gap in an optical Roots blower. The three-dimensional unsteady CFD model of the Roots b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, a series of factors deteriorating the results of the PIV test were highlighted, such as limitations in resolving flow features in regions near the gaps and the large sample size required. Numerical analyses of a Roots blower were carried out by Sun et al [14]. It is observed that the CFD flow field agrees with experimental results in the flow pattern and velocity magnitude at certain areas but overestimates the leakage flow velocity.…”
Section: Introductionmentioning
confidence: 73%
“…However, a series of factors deteriorating the results of the PIV test were highlighted, such as limitations in resolving flow features in regions near the gaps and the large sample size required. Numerical analyses of a Roots blower were carried out by Sun et al [14]. It is observed that the CFD flow field agrees with experimental results in the flow pattern and velocity magnitude at certain areas but overestimates the leakage flow velocity.…”
Section: Introductionmentioning
confidence: 73%
“…The investigations of Stosic 2 and Pascu et al 12 have shown that the use of new techniques for rotors profiling helped to manufacture rotors of complex shapes with tolerances of the order of few microns, which improved efficiencies. Also, a limited number of the previous investigations have been carried out 19,20 to characterise flow leakages using experiments and CFD simulations. The gas pulsations are also a main source of noise within the discharge cavity and have been investigated since 1986 by many authors.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of flow through the male rotor housing clearance of screw machines was carried out by Utri [11] who compared simulation results with flow pictures obtained using the Schlieren method. Recently, an experimental and numerical study of a roots blower in actual running condition was carried out by Sun et al [12], They implemented the PIV technique for clearance flow visualization. A series of factors deteriorating the results of the PIV test were observed such as the surface flaws of the transparent window, the reflection of the surface, the jitter in the phase-locking due to uncertainties in the transmission of the synchronized gear, the accumulation of the liquid particles and the pressure fluctuations.…”
Section: Introductionmentioning
confidence: 99%